Analysis of Water Utilization as a Source of Energy - Rudy Laksmono Widayatno; I Wayan Midhio; Yanif Dwi Kuntjoro (The Republic of Indonesia Defense University, 2016)
Micro-hydro as one form of renewable energy and could be developed, it is important as a new knowledge so that it can know to the public. This study shows how the feasibility of micro hydro system to be built in the communities to provide benefits to the safety and well-being. Feasibility study covering aspects of the social environment, the technology and its benefits. Through the simulation of the application of micro hydro power plant (MHP) in the Indonesian Defence University (IDU), this study intends to find empirical data is about the design of the MHP can be implemented. This research reveals about the type of MHP in accordance with the demographic conditions in the IDU.